2019
DOI: 10.1101/560623
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Brain Aging in Major Depressive Disorder: Results from the ENIGMA Major Depressive Disorder working group

Abstract: 222Background: Major depressive disorder (MDD) is associated with an increased risk of brain atrophy, 223 aging-related diseases, and mortality. We examined potential advanced brain aging in MDD patients, and 224 whether this process is associated with clinical characteristics in a large multi-center international dataset. 225Methods: We performed a mega-analysis by pooling brain measures derived from T1-weighted MRI 226 scans from 29 samples worldwide. Normative brain aging was estimated by predicting chronol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 56 publications
(82 reference statements)
2
8
0
Order By: Relevance
“…Other approaches currently used in ENIGMA include brain structural covariance analysis graph theory approach for intra-individual brain structural covariance networks in OCD 77,143 , sulcal morphometry 144 , hippocampal subfield analysis [80][81][82]145 and disease effects on lateralization (in OCD, MDD, and ASD) 71,90,97 . More recently, ENIGMA's Brain Age WG was formed to apply various algorithmic estimators of 'brain age' across several ENIGMA WGs 72 . From the ENIGMA-Brain Injury group, the MR spectroscopy (MRS) WG has formed to focus on the harmonization of MRS data which could reach across other WGs in the future.…”
Section: Enigma-methods Focused Working Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other approaches currently used in ENIGMA include brain structural covariance analysis graph theory approach for intra-individual brain structural covariance networks in OCD 77,143 , sulcal morphometry 144 , hippocampal subfield analysis [80][81][82]145 and disease effects on lateralization (in OCD, MDD, and ASD) 71,90,97 . More recently, ENIGMA's Brain Age WG was formed to apply various algorithmic estimators of 'brain age' across several ENIGMA WGs 72 . From the ENIGMA-Brain Injury group, the MR spectroscopy (MRS) WG has formed to focus on the harmonization of MRS data which could reach across other WGs in the future.…”
Section: Enigma-methods Focused Working Groupsmentioning
confidence: 99%
“…A follow-up analysis on a subset of these aforementioned data found that the brain MRIs of adult patients with MDD (18-75 years old) appeared, on average, 1.08 years older than those of controls (d = 0.14) 72 . This 'brain age' estimate was based on a machine learning algorithm trained to predict chronological age from morphometric data from 2188 controls across 19 cohorts and subsequently applied to hold-out data from 2126 healthy controls and 2675 people with MDD.…”
Section: Enigma-mddmentioning
confidence: 99%
“…Hibar et al 2,68 Volumetric reductions in hippocampus and thalamus and enlarged lateral ventricles in patients; thinner cortical gray matter in bilateral frontal, temporal and parietal regions; strongest effects on left pars opercularis, fusiform gyrus and rostral middle frontal cortex in BD. 67 ; Tozzi et al 75 ; Han et al 72 ; Frodl et al 74 ; Renteria et al 172 ;…”
Section: Introductionmentioning
confidence: 99%
“…However, across the studies examining subcortical, cortical and white matter integrity differences in MDD 33,47,48,82 , despite high statistical power, we found no diagnosis-by-sex interaction effects in adult MDD patients, indicating that structural brain alterations likely do not contribute to these sex differences in MDD. In addition, even though the model fits of the brain aging models improved when trained separately in males and females, the (subtle) advanced brain aging that we observed in adults with MDD was not different for male versus female patients 93 . Nonetheless, sex differences in structural brain alterations may be present during specific sensitive periods of brain development, such as adolescence or more specifically, during puberty 105 .…”
Section: Sex Differences In Depression-related Structural Brain Altermentioning
confidence: 72%
“…Therefore, we examined deviations from normative brain aging in adults with MDD and associated clinical heterogeneity by pooling data from >6,900 healthy controls and individuals with MDD from 19 research cohorts and 22 different scanners participating in the ENIGMA MDD consortium 93 . Normative brain aging was estimated by predicting chronological age (18-75 years) from seven subcortical volumes, 34 cortical thickness and 34 surface area, lateral ventricles and ICV male controls and 986 males with MDD, and 1,199 female controls and 1,689 females with MDD from the ENIGMA MDD consortium; correlations r between predicted and actual age ranged from 0.77-0.85; Mean Absolute Errors (MAE) ranged from 6.32-7.18 years), as well as to completely independent samples from different scanning sites (N=1,330 from 23 different scanners; r=0.71 and MAE=7.49 for male controls, r=0.72 and MAE=7.26 for female controls)93 . patients with more extreme patterns of brain aging, which would be important to identify as accelerated brain aging may be reversed with targeted treatment.…”
mentioning
confidence: 99%